Fitness effects of assisted gene flow in an endangered salmonid population - Klemme, Ines; Pysäys, Joonas; Hyvärinen, Pekka; Karvonen, Anssi (Wiley, 2024)
Assisted gene flow is increasingly used to combat severe population declines. However, the associated risks, such as outbreeding depression, are often insufficiently assessed. Here, we studied the impact of assisted gene flow on the fitness of a highly endangered landlocked salmon population (Salmo salar m. sebago) from the lake Saimaa complex (Finland), using an anadromous Atlantic salmon population (S. salar) as donor. We released individuals of both parental populations and their hybrids into seminatural streams, monitoring their survival under predation risk from Northern pike (Esox lucius) and their growth on a natural diet. Before release, we exposed half of the salmon to the parasite Diplostomum pseudospathaceum to study whether assisted gene flow affects infection susceptibility, which could indirectly shape predation susceptibility and growth. The parental populations differed in both studied traits and the hybrids showed intermediate values. Relative to the target landlocked salmon population, hybrids experienced 21–26% lower survival, but 1.4–2.2% higher growth. They also carried 0.6–2.8 more parasites than the landlocked salmon, contributing to survival differences. These findings indicate that assisted gene flow can induce both negative and positive fitness effects. We propose that the overall net effects of this conservation tool need to be carefully evaluated before its implementation. peerReviewed